THE INFLUENCE OF WORK ETHICS, WORK ENGAGEMENT AND PERSONALITY ON EMPLOYEE PERFORMANCE - Jufrizen, Jufrizen; Erika, Virza (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
The purpose of this study was to determine and analyze the effect of work ethics, work involvement and personality on employee performance (study at the Medan City Regional Tax and Retribution Management Agency). The approach used in this study is an associative approach. The population in this study were employees of the Medan City Regional Tax and Retribution Management Agency)., A total of 32 employees while the sample in this study used Nonprobability sampling or Saturated Sampling as many as32 Employees. The data collection technique in this study used a questionnaire technique by distributing questionnaires. The data analysis technique in this study uses Multiple Linear Regression Test, Hypothesis Testing (T Test and F Test), and Coefficient of Determination. Data processing in this study using IBM SPSS Statistic 23 software program. The results of this study prove that partially work ethics (X1) has an effect on performance (Y) with t-test work ethics (X1) 1.954 > ttable 1.693 with sig 0.008 < 0, 05, and Work Involvement (X2) 2,348 > t table 1,693 with sig 0,089 < 0,05. and Personality (X3) 1,880 > ttable 1,693 with sig 0,006 < 0,05. The results of this study prove that simultaneously Fcount 7.142 > Ftable 4.20 with R Square 0.509 or 50.9% which means that there is an influence of work ethics.